The influence of childhood trauma and epigenetic variation in OXTR on anxiety proneness and structural neuroimaging measures in a South African adolescent cohort - Rust, Thomas Martin (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.